Sustainable Development of the Mountain Territory of the Ukrainian Carpathians: Foreign Experience and Domestic Realities - Chervinska, Inna; Chervinskyi, Andrii (Journal of Vasyl Stefanyk Precarpathian National University, 2018)
The article describes the factors and indicators of sustainable development of mountain areas. The authors analyse the experience of foreign countries in the educational and socio-cultural activities of the inhabitants of the mountains, determine the prospects for its implementation in the mountainous regions of the Ukrainian Carpathians. The researches determine the ways and prospects of development of mountain territories of the Ukrainian Carpathians compare foreign experience of some European countries and the United States on sustainable development. The purpose of the article is based on studying the experience of mountainous countries, identifying the leading factors influencing their sustainable development and revealing the prospects for their implementation in the mountainous regions of the Ukrainian Carpathians. In accordance with the purpose of the study, features of mountain areas were outlined, the factors that determine the specifics of their educational, ecological, economic and socio-cultural development are described. The authors analysed international experience of managing the development of mountain areas in order to determine the possibilities of its use in national practice